2014
DOI: 10.1038/boneres.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screening of mouse gene knockouts identifies established and novel skeletal phenotypes

Abstract: Screening gene function in vivo is a powerful approach to discover novel drug targets. We present high-throughput screening (HTS) data for 3 762 distinct global gene knockout (KO) mouse lines with viable adult homozygous mice generated using either gene-trap or homologous recombination technologies. Bone mass was determined from DEXA scans of male and female mice at 14 weeks of age and by microCT analyses of bones from male mice at 16 weeks of age. Wild-type (WT) cagemates/littermates were examined for each ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 316 publications
6
104
1
Order By: Relevance
“…11 Previous studies 11,13 examined Tph2 KO mice at 4 to 16 weeks of age, whereas Lexicon's mice were examined at 18 through 83 weeks of age. Tph2 KO mice have a transient growth retardation starting a few days after birth and lasting through 4 months of age 18,19 and limited data from Lexicon's KO mouse screening analyses 16 support this finding. Low trabecular bone Modest skeletal phenotypes in adult Tph2 KO mice R Brommage et al mass in studies examining growing mice is possibly related to their small size.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…11 Previous studies 11,13 examined Tph2 KO mice at 4 to 16 weeks of age, whereas Lexicon's mice were examined at 18 through 83 weeks of age. Tph2 KO mice have a transient growth retardation starting a few days after birth and lasting through 4 months of age 18,19 and limited data from Lexicon's KO mouse screening analyses 16 support this finding. Low trabecular bone Modest skeletal phenotypes in adult Tph2 KO mice R Brommage et al mass in studies examining growing mice is possibly related to their small size.…”
Section: Discussionsupporting
confidence: 62%
“…Data obtained during highthroughput screening. 16 Equal numbers of male and female mice were examined for each genotype at each age, with Ns ¼ 4 for WT and Ns ¼ 8 for KO mice. Po0.001 at 2 weeks and P ¼ 0.02 at 4 weeks of age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These transporters control the uptake and efflux of many critical ions or substrates during amelogenesis and have been determined to result in enamel abnormalities if mutated. Mutations in SLC4A4 result in pigmentation differences and a propensity to fracture (21,(42)(43)(44)(45)(46). Patients with proximal renal tubular acidosis (pRTA) caused by mutations in SLC4A4 also exhibit dental abnormalities (5,42).…”
Section: Discussionmentioning
confidence: 99%
“…However, an association among LRP5 deficiency, circulating 5HT and bone loss has not been reproduced in mice with osteocyte-specific expression of inducible Lrp5 mutations that cause high and low bone mass phenotypes in humans [3]. Further, association between circulating serotonin and bone mass has not been unequivocally confirmed in different mouse knockout models (global knockouts of TPH1 and TPH2, LRP5) [4][5][6]. De Vernejoul and colleagues revisited the bone phenotype in mice with genetic deletion of peripheral 5HT-synthesizing enzyme tryptophan hydroxylase-1 (TPH1 -/-) and showed that osteoclasts synthesize 5HT which acts to induce osteoclast precursor differentiation in a local micro-serotoninergic system via a mechanism of RANKL-induced osteoclast formation [7].…”
Section: Introductionmentioning
confidence: 98%